Wireless battery-free body sensor networks using near-field-enabled clothing - Rongzhou Lin (Nature Portfolio, 2020)
Though wireless near-field communication (NFC) technologies that connect wearable sensors for health monitoring have been reported, the short range of NFC readers limits sensor functionality. Here, the authors report a wireless and battery-free body sensor network with near-field-enabled clothing.